Major Classes of Sourdough Enzymes - Aspri, Maria; Tsaltas, Dimitrios (My University, 2023)
The enzymatic and microbial conversion of flour components during the bread making process affects bread quality (rheology, texture, flavor). The action of cereal enzymes and the metabolism of sourdough bacteria are interdependent. The activity of cereal enzymes is modulated by microbial acidification, oxygen consumption, and the accumulation of thiols by microbial metabolism. Cereal enzymes, in turn, provide substrates for bacterial growth, and their activity contributes to the selection of fermentation microbiota. This chapter reviews the main classes of cereal enzymes available in sourdough, cereals, and the bread making process as well as the metabolism of lactic acid bacteria in the conversion of carbohydrates, proteins, phenolic compounds, and lipids.